Detecção precoce de perda auditiva em trabalhadores expostos a agrotóxicos com uso de audiometria de altas frequências - Sena, Tereza Raquel Ribeiro de (2017)
INTRODUCTION: Health impacts caused by the use of pesticides are large. Studies have demonstrated the effect of pesticides associated with other harmful agents, however, if assumes that, in isolation, the pesticides can also be harmful to hearing. As the high-frequency Audiometry (AAF) is a procedure used in the clinical diagnosis of hearing loss caused by chemical agents, was studied the possibility of the contribution of this resource in the detection of hearing loss caused by pesticides. OBJECTIVE: Evaluate hearing health of rural workers with and without exposure to pesticides. MATERIAL AND METHODS: Cross-sectional study that has met the criteria of research ethics, and had no conflict of interest, was held in 87 workers, aged 18 to 59 years, with formal, informal working and/or on family farming. Were evaluated 87 workers not exposed to pesticides (Group 1) and 49 that had exposure to these products (Group 2), whose have done anamnesis, ear canal inspection, distortion product otoacoustic emissions (DPOAE), pure tone audiometry at 0.5K, 1K, 2K, 3K, 4K, 6K and 8KHz, being normal, high frequency audiometry at 9K, 10K, 11,2K, 12,5K, 14K, 16K, 18K and 20KHz. RESULTS: The workers were distributed in 41% of the males and 59% female; 54% worked in agriculture (p < 0.0001), the mixture of pesticides was reported by 77% of the examined, the glyphosate based product was the most used (73%) and 24% did not know inform the name of the pesticide used, the use of personal protective equipment has not been identified, the average age of onset was 11 years (SD = 3.89), the glyphosate-based product was the most used (73%) and 24% did not know inform the name of the pesticide used. The use of personal protective equipment has not been identified, the average age of onset was 11 years (SD = 3.89) and 23% of the subjects (p = 0.013) reported dizziness before, during or after the application of pesticides. Workers exposed to pesticides (G2) showed higher averages in the AAF thresholds than those who were not exposed (G1) with significance between 9,000 and 20,000 Hz in both ears (p < 0.0001), regardless of the age group. The results of DPOAE and other symptoms were not significant. CONCLUSION: Workers exposed to pesticides showed worse results in the AAF, when compared with those without exposure. The AAF can be considered a sensitive instrument to detect auditory changes in workers exposed to pesticides.